Postnatal Care Practices in Magar and Gurung Communities: A Case Study of Kaski District - Baral, Om Prasad (Academic Voices: A Multidisciplinary Journal, 2015)
This paper focuses on postnatal care awareness and practices of Magar and Gurung communities at Pumdi Bhumdi VDC in Kaski district. Both indigenous groups are suffering from different kinds of postnatal problems. The findings reveal that awareness and practices related to postnatal care were not satisfactory. Majority of the Magar and Gurung mothers were not aware of postnatal checkup. Gurung mothers seemed to be more aware than Magar mothers on immunization schedule. Most of the Magar mothers were found using razor or blade and knife or sickles which are medically unsterilized for cutting umbilical cord whereas one half of the Gurung mothers were using sterilized blade. DOI: http://dx.doi.org/10.3126/av.v4i0.12355 Academic Voices Vol.4 2014: 37-41